Quantitative characterization of dispersed particle size, size distribution, and matrix ligament thickness in polypropylene blended with metallocene ethylene-octene copolymers - K. Premphet (2018)
The average rubber particle size, size distribution, and matrix ligament thickness between particles in polypropylene blends containing metallocene catalyzed ethylene-octene copolymers have been quantitatively analyzed, as function of blend composition and phase viscosity ratio. Comparison has been made between experimental data and those predicted from a number of theoretical models. All blends showed two-phase morphology, with interestingly a bimodal distribution of the rubber particle size. The ranges and averages of rubber particle size were mainly determined by blend composition and viscosity ratio between the phases, irrespective of comonomer content along the rubber chains. The logarithmic relationship between the matrix ligament thickness and rubber concentration was observed. The values of ligament thickness obtained from the experiments and theoretical models were not in agreement.